Angiotensin-I-Converting Enzyme Inhibitory and Antioxidant Activities of Protein Hydrolysate from Muscle of Barbel (Barbus callensis). (18th September 2013) - Sila, Assaad; Haddar, Anissa; Martinez-Alvarez, Oscar; Bougatef, Ali
Abstract : The present study investigated angiotensin-I-converting enzyme (ACE) inhibitory and antioxidant activities of barbel muscle protein hydrolysate prepared with Alcalase. The barbel muscle protein hydrolysate displayed a high ACE inhibitory activity (C I 50 = 0.92  mg/mL). The antioxidant activities of protein hydrolysate at different concentrations were evaluated using various in vitro antioxidant assays, including 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical method and reducing power assay. The barbel muscle protein hydrolysate exhibited an important radical scavenging effect and reducing power. These results obtained by in vitro systems obviously established the antioxidant potency of barbel hydrolysate to donate electron or hydrogen atom to reduce the free radical. Furthermore, these bioactive substances can be exploited into functional foods or used as source of nutraceuticals.